2009
DOI: 10.1159/000197873
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Gene Polymorphism Is Less Frequent in Children Born Small for Gestational Age without Catch-Up Growth

Abstract: Background/Aims: Glucocorticoids are important regulators of many processes involved in embryonal growth and development and fat and glucose metabolism. Glucocorticoids exert their effect through the glucocorticoid receptor (GR). The aim of this study was to investigate possible associations between 4 well-known GR gene haplotypes and size at birth. Methods: We investigated associations between GR haplotypes and size at birth in a Dutch reference cohort. This reference cohort consisted of 222 young healthy Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…We did not find this association. Our pilot study in a group of 119 SGA children showed a lower frequency of the Bcl1 polymorphism than the controls (22). A previous cohort study in the general population showed that carrying a GR haplotype including the Bcl1 polymorphism was associated with a smaller size at birth corrected for gestational age.…”
Section: Discussionmentioning
confidence: 38%
“…We did not find this association. Our pilot study in a group of 119 SGA children showed a lower frequency of the Bcl1 polymorphism than the controls (22). A previous cohort study in the general population showed that carrying a GR haplotype including the Bcl1 polymorphism was associated with a smaller size at birth corrected for gestational age.…”
Section: Discussionmentioning
confidence: 38%